2015
DOI: 10.1177/1078155215577809
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with optimized tacrolimus dosing in hematopoietic stem cell transplantation

Abstract: Objective The primary objective was to analyze the initial tacrolimus concentrations achieved in allogeneic hematopoietic stem cell transplantation patients using the institutional dosing strategy of 1 mg IV daily initiated on day +5. The secondary objectives were to ascertain the tacrolimus dose, days of therapy, and dose changes necessary to achieve a therapeutic concentration, and to identify patient-specific factors that influence therapeutic dose. The relationships between the number of pre-therapeutic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Butts et al examined their institutional practice using initial 1 mg FD TAC to achieve the target serum level of 10–15 ng/mL( 18 ), which they concluded required at least two dose adjustments and a median of 10 days to achieve. We found that lower TISS (<10 ng/mL) was as effective with less toxicity than higher (≥10 ng/mL), and that TISS <10ng/mL did not affect engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butts et al examined their institutional practice using initial 1 mg FD TAC to achieve the target serum level of 10–15 ng/mL( 18 ), which they concluded required at least two dose adjustments and a median of 10 days to achieve. We found that lower TISS (<10 ng/mL) was as effective with less toxicity than higher (≥10 ng/mL), and that TISS <10ng/mL did not affect engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Weight-based dosing (WBD) has been utilized with TAC when combined with sirolimus or methotrexate( 12 , 17 ), while an initial flat dose (FD) of 1 mg TAC has been used in PTCy-based regimens( 2 , 18 ). However, TAC dosing is not standardized in PTCy-based regimens, and it is unknown whether different dosing strategies correlate with specific therapeutic TAC levels at initial steady state (TISS).…”
Section: Introductionmentioning
confidence: 99%
“…Both supratherapeutic and subtherapeutic tacrolimus concentrations can result in poor outcomes. Elevated steady-state trough concentrations of tacrolimus are associated with increased risk of adverse effects, including nephrotoxicity, hepatotoxicity, electrolyte abnormalities, and neurotoxicity, while subtherapeutic levels may increase the risk of developing GVHD and graft rejection ( Kernan et al, 1986 ; Kernan et al, 1987 ; Butts et al, 2016 ; Andrews et al, 2018 ). Beyond intrinsically high PK variability, tacrolimus is primarily metabolized hepatically by cytochrome p450 3A4 and 3A5 (CYP3A4/5) and is, therefore, susceptible to many drug-drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…5 Other dosing strategies that have been employed include 1 mg CIVI daily for all patients, resulting in 98% of patients with subtherapeutic levels 48 hours after initiation based on a lower target range of 5-15 ng/mL. 6 Another factor that must be considered when initiating tacrolimus is that it undergoes extensive metabolism by the cytochrome P450 CYP3A enzyme subfamily and by p-glycoprotein. 7 Thus, tacrolimus dosing is also complicated by potentially significant drug-drug interactions with post-alloHSCT supportive medications including azole antifungals.…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, tacrolimus dosing is also complicated by potentially significant drug-drug interactions with post-alloHSCT supportive medications including azole antifungals. [6][7][8][9] Diarrhea, a common ailment during alloHSCT, has been associated with elevated tacrolimus levels in solid organ transplant recipients, but has not been well studied in alloHSCT patients. 10 Other factors that may influence tacrolimus pharmacokinetics include the type of body weight used in weight-based dosing and the timing of initial administration in relation to transplantation and/or azole antifungal initiation.…”
Section: Introductionmentioning
confidence: 99%